2022
DOI: 10.3390/clinpract12050078
|View full text |Cite
|
Sign up to set email alerts
|

Glomangioma Supply from Profunda Femoris Artery in Peripheral Artery Disease

Abstract: This is a case report of a 5.6 cm glomangioma supplied by the femoral profunda artery in a 66-year-old male patient with severe peripheral artery disease. The patient complained of discomfort and mild pain at the place of the lesion and an accelerated growth rate in the last two months. A nodular mass located laterally on the left foot, elastic, covered with a thin skin, and mobile, was noted on the clinical exam. Doppler exam demonstrated an active vascular supply. CT angiography showed a femoral profunda art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They concluded that uterine artery pseudoaneurysm should always be considered in cases of unexplained abdominal pain after surgery or childbirth with or without vaginal bleeding. Lungu et al [ 28 ] published a case report of a 5.6 cm glomangioma supplied by the femoral profunda artery in a 66-year-old male patient with severe peripheral artery disease. The patient complained of discomfort and mild pain at the place of the lesion and an accelerated growth rate in the last two months.…”
mentioning
confidence: 99%
“…They concluded that uterine artery pseudoaneurysm should always be considered in cases of unexplained abdominal pain after surgery or childbirth with or without vaginal bleeding. Lungu et al [ 28 ] published a case report of a 5.6 cm glomangioma supplied by the femoral profunda artery in a 66-year-old male patient with severe peripheral artery disease. The patient complained of discomfort and mild pain at the place of the lesion and an accelerated growth rate in the last two months.…”
mentioning
confidence: 99%